A Cratered Photonic Crystal Cavity Mode for Nonlocal Exciton–Photon Interactions. Issue 2 (5th June 2019) - Qian, Chenjiang; Xie, Xin; Yang, Jingnan; Xu, Xiulai
Abstract: Optical nanocavities for coherent interfaces usually have their electric field maximum at the center point, which normally benefits interactions with small local quantum emitters. Here, a partial thickness modulation on 2D slab photonic crystal cavities for a cratered cavity mode function to improve nonlocal interactions is proposed. The thickness modulation is applied around the central region, and has little effect on the fringe electric field, which determines the coupling to waveguides or other cavities. Furthermore, the partial modulation enhances the cratered electric field at positions that are distant from the center point. Therefore, interactions with multiple separated emitters are simultaneously enhanced, and the interaction with a large emitter beyond the dipole approximation is also doubled. The improvement of the nonlocal interactions demonstrates a great potential for the cratered cavity mode profile for applications in quantum photonic networks. Abstract : A partial thickness modulation on photonic crystal cavities for a cratered cavity mode function to improve nonlocal interactions is proposed. The modulation greatly enhances interactions with multiple separated emitters or a large emitter beyond the dipole approximation, while has little effect on the node connections in photonic network. These results demonstrate great potentials for the applications in quantum networks.